SiOCN Functionalized Carbon Nanotube Gas Sensors for Elevated Temperature Applications. Issue 4 (26th December 2014) - Karakuscu, Aylin; Hu, Lung‐Hao; Ponzoni, Andrea; Baratto, Camilla; Ceccato, Riccardo; Sberveglieri, Giorgio; Raj, Rishi; Riedel, R.
<x xml:space="preserve">Abstract</x> Silicon Oxycarbonitride (SiOCN) functionalization is proposed for stable, reproducible, reliable, and enhanced gas‐sensing properties in carbon nanotube (CNT) gas sensors. The process is very simple: liquid precursor completely coats the surfaces of the CNTs without requiring any surface modification and a thin layer of semiconductor ceramic SiOCN is created on the CNTs after heat treatment. This new kind of conductometric gas sensors can detect 10 ppm NH3 and 2 ppm NO2 at temperatures up to 350°C. The stability of the functionalized CNT sensor is verified up to 520°C, while the CNT sensor without the SiOCN coating lost conductance after 250°C due to the structural modification. SiOCN functionalization of CNT changes the recovery from irreversible to reversible and the recovery time decreases from 60 min at 100°C to 19 min at 350°C.